2014
DOI: 10.1039/c4cp02298j
|View full text |Cite
|
Sign up to set email alerts
|

Photoisomerization and structural dynamics of two nitrosylruthenium complexes: a joint study by NMR and nonlinear IR spectroscopies

Abstract: In this work, the photoisomerization and structural dynamics of two isomeric nitrosylruthenium(ii) complexes [Ru(OAc)(2cqn)2NO] (H2cqn = 2-chloro-8-quinolinol) in CDCl3 and DMSO are examined using NMR and IR spectroscopic methods. The two N atoms in the 2cqn ligand are in trans position in the synthesized cis-1 isomer, while they are in cis position in the cis-2 isomer. Kinetics monitored by NMR spectroscopy shows that the rate constant of photoisomerization from cis-2 to cis-1 isomer depends on the wavelength… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 60 publications
3
23
0
Order By: Relevance
“…The results show that the T 1 time of the NO stretching vibrational state relaxes on the order of 7-10 ps, showing less than 30% variation from one isomer to another. It is well known that vibration energy relaxation involves both intramolecular and intermolecular energy-dissipation channels [28], the former is usually called intramolecular vibration redistribution (IVR) and the latter is called intermolecular vibrational energy relaxation (IVE). In the present case, the vibrational energy of excited NO stretching most likely relaxes through IVE, thus how the NO group interacts with solvent should be important.…”
Section: Magic-angle Pump-probe Spectramentioning
confidence: 99%
See 2 more Smart Citations
“…The results show that the T 1 time of the NO stretching vibrational state relaxes on the order of 7-10 ps, showing less than 30% variation from one isomer to another. It is well known that vibration energy relaxation involves both intramolecular and intermolecular energy-dissipation channels [28], the former is usually called intramolecular vibration redistribution (IVR) and the latter is called intermolecular vibrational energy relaxation (IVE). In the present case, the vibrational energy of excited NO stretching most likely relaxes through IVE, thus how the NO group interacts with solvent should be important.…”
Section: Magic-angle Pump-probe Spectramentioning
confidence: 99%
“…The original coordinates of atoms in the cis-1, cis-2 and trans isomeric complexes were obtained from the crystal structures determined with X-ray diffraction [26][27][28][29][30][31]. Visualization was performed with GaussView 5.0 [33].…”
Section: Theoretical Calculationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our recent works, a similar Ru-NO complex with cis and trans configurations has been examined using ultrafast IR spectroscopies. It was found that nonlinear IR signatures (spectral line width, dynamical parameters), especially those extracted from 2D IR spectra, can be used to differentiate the cis and trans configurations .…”
Section: Introductionmentioning
confidence: 99%
“…The light irradiation time was 60 min in the wavelength of 420 nm filter and 30 min with Xe lamp. The quantum yield of two complexes were estimated at the wavelength of λ = 420 nm according to the equation: Φ 420 nm = n N A h c/E λ (where n was the number of reactant molecules in mol, N A was Avogadro constant, h was Plank constant, c was the speed of light and E was the absorbed photon energy), in which the absorbed photon energy was obtained by the formula E = I t S T (I was the power density of incident light; t was the time; S was the effective absorption area; T was the transmittance) [ 56 ].…”
Section: Methodsmentioning
confidence: 99%